Studies on the Derveni Papyrus: Volume 2 - Most, Glenn W.; Janko, Richard; Piano, Valeria (Oxford University Press, Incorporated, 2022)
Studies on the Derveni Papyrus, Volume II brings together two new editions of the first fragmentarily extant columns of the Derveni Papyrus and seven scholarly articles devoted to their interpretation.